2012
DOI: 10.1002/lary.23252
|View full text |Cite
|
Sign up to set email alerts
|

Rapid salivary pepsin test: Blinded assessment of test performance in gastroesophageal reflux disease

Abstract: Rapid LFD for salivary pepsin has acceptable test characteristics in patients with GERD. A positive salivary pepsin test in this group may obviate the need for more expensive diagnostic testing by EGD or pH monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 21 publications
2
104
1
6
Order By: Relevance
“…Pepsin shows proteolytic activity up to a pH of 6 and salivary pepsin tests have shown increased pepsin concentrations in patients with GORD and GORD-related supra-oesophageal pathologies. [31][32][33][34] In a recent ex vivo study the additive erosive effects of pepsin and trypsin on teeth were shown. 35 Further elaboration of the interaction of the erosive effects of acid with other salivary factors is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Pepsin shows proteolytic activity up to a pH of 6 and salivary pepsin tests have shown increased pepsin concentrations in patients with GORD and GORD-related supra-oesophageal pathologies. [31][32][33][34] In a recent ex vivo study the additive erosive effects of pepsin and trypsin on teeth were shown. 35 Further elaboration of the interaction of the erosive effects of acid with other salivary factors is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The blue lines are visible on the display because the monoclonal antibody is directly labelled with blue latex beads, which detach at the time of Ag-Ab binding. Saritas Yuksel et al [19] evaluated the PEP-Test (defined as ELISA LFD) in 47 patients using pH-metry as a reference standard. The results were compared with a control population, which underwent only the PEP-Test, which has sensitivity and a specificity of 87% ( Figure 5).…”
Section: Pep-testmentioning
confidence: 99%
“…In this context, the advent of novel esophageal function testing, such as impedance-pH monitoring (MII-pH) and high resolution manometry (HRM), has allowed for relevant progress in the understanding of the pathophysiological mechanisms contributing to the development of GERD and, thereafter, its diagnosis and management. Moreover, the role of new technology to detect laryngopharyngeal reflux (LPR) [16][17][18] , as well as the presence of pepsin in clinical samples [19] , deserves careful consideration. The aim of the present review article is to report on the current literature about recent advances in diagnosing GERD.…”
Section: Introductionmentioning
confidence: 99%
“…This is an innovative diagnostic device, based on immune-enzymatic test (i.e. using monoclonal antibodies) able to detect the presence of pepsin in a saliva sample with a sensitivity and specificity of, respectively, 88 and 87% [17]. It is a rapid and non-invasive test.…”
Section: Introductionmentioning
confidence: 99%